6 - The Public Space in Nigeria: Politics of Power, Gender and Exclusion - Alubo, Ogoh (Africa Development, 2021)
The public space often conveys a notion of res publica, owned by all members of the public, with equal access and participation. In reality, however, there are several publics, as indeed spaces at the local, state, national and international levels. Irrespective of levels, the public space is where decisions binding on all are taken, executed and evaluated. It is an arena where the various publics struggle to have control over and participate in. Access to and participation in the public space in Nigeria is frequently conceived as part of the national question and speak to the nature of integration in one country where all constituent units have a sense of belonging. It is here argued that Nigeria’s public space is a contested terrain, access to which reflects all the known divides in society: gender, class, religion and ethnicity. These divides become the important determinants of access as well as the nature and quality of participation. Some of these contestations have led to explosions of violence, pitting indigenes against settlers, one ethnic group against the other(s), as well as Christians against Muslims. These experiences, including those of women’s participation in the political process and struggles for a common citizenship in one Nigeria, are used as illustra- tions of the contest over public space. It is concluded that participation in and control of the public space must be recognized as part of the broader issues of citizenship rights and gender equality in society. The Nigerian experience has important lessons for the rest of the African continent which is stuck in several conflicts, most of them over access and control of national-territorial public space.